METODE EXPERIENTAL LEARNING DALAM PROSES PEMBELAJARAN MENULIS PARAGRAF NARASI BAHASA JERMAN SISWA KELAS XI SMAN 12 SURABAYA - MURIYATIN, (LATERNE, 2016)
Writing skills in a foreign language is the most difficult skill in learning. The students have  difficulty  in  finding  the  ideas  to  write,  especially  in  Paragraf Narrative writing . One method of learning that can be applied is Experiential Learning Method. This method can be applied upon giving the material in the classroom as well as in the form of paragraph narrative writing exercises to be done individually by pouring what is in his thoughts into an article based on their personal experiences , respectively. The statement of problem in this research is “how the process of learning to write Narrative Paragraphs in German Language using Experiential Learning Method for student in class XI of SMAN 12 Surabaya?”. This study aims “to determine the process of learning to write Narrative Paragraphs in German Language using Experiential Learning Method for student in class XI of SMAN 12 Surabaya”. This study is a qualitative descriptive study and performed a total of 4 meetings . The research instrument is a non-test , the use of instrument is the observation student observation sheet . Observation results of research data and documentation for use Experiental Learning Methods in paragraph narrative writing skills German. The research data is analyzed using qualitative descriptive approach . The number of students in this study is 29 students . During the four times meet sessions, students were given a lesson by using Experiential Learning method.  The  results  showed  that  the Experiental  learning method has been well implemented according in accordance with step stride. The result of the  observation  showed  that  the  students became  more  active  during  the  learning  process. The  students came to like learning German language with Experiental  learning method, especially in writing. Student learning outcomes of each meeting has increased, although there are some errors in the writing like writing Articles and placement uppercase. So, it can beconcluded that Experiental  learning method can be used as an alternative in learning Germanlanguage, especially in the teaching of writing skills. Keywords : Writing Skills , Naration Paragraph, Experiental Learning method